2020
DOI: 10.3177/jnsv.66.32
|View full text |Cite
|
Sign up to set email alerts
|

The Association with Dietary Patterns and Risk of Anemia in Japanese Elderly

Abstract: Anemia is a risk factor for frailty. Although various factors can reduce the risk of anemia, information on dietary contributions is limited. This study aimed to evaluate the association between anemia and eating patterns in Japanese elderly. Our study included 6,864 elderly individuals, aged $65 y, whose data were obtained from the 2010-2015 National Health and Nutritional Survey, Japan. Anemia was defined as whole blood hemoglobin concentrations ,13 g/dL in men, and ,12 g/dL in women. We classified eating pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…We investigated the association between LS and anemia among community‐dwelling older adults. In the LS group, the prevalence of anemia was 23.0%, which is higher than the 10% 19 or 15.2% 20 prevalence reported in previous studies on older adults aged ≥65. After adjusting for confounding factors, older adults with anemia had significantly higher rate of LS than those without anemia.…”
Section: Discussioncontrasting
confidence: 69%
“…We investigated the association between LS and anemia among community‐dwelling older adults. In the LS group, the prevalence of anemia was 23.0%, which is higher than the 10% 19 or 15.2% 20 prevalence reported in previous studies on older adults aged ≥65. After adjusting for confounding factors, older adults with anemia had significantly higher rate of LS than those without anemia.…”
Section: Discussioncontrasting
confidence: 69%
“…18 The prevalence of anemia increases with age, is higher in men than in women 17 and is higher in blacks people than in white people, although most of the individuals classified as having anemia using the WHO criteria only have mild anemia. 18 The prevalence of anemia in older adults has been reported to be 17.1% (>65 years), 19 22.3% (69-91 years) 20 in Japan and 12.9% (>60 years) in the rural areas of China, 21 which are comparable to the prevalence rates in Western countries.…”
Section: Prevalence Of Anemia In Older Adultsmentioning
confidence: 88%
“…Vegetarians are more likely to develop iron-deficiency anemia [50]. Studies in China [51] and Japan [11] have both shown that a rice-based diet has a harmful effect on anemia. However, a study in India showed that increased consumption of coarse cereals could reduce anemia prevalence in Indian women.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Mexico found that the Western dietary pattern (mainly characterized by sweet drinks, salty snacks, charcuterie, fast food, and cereals/tubers) was positively associated with anemia in girls aged between 12 and 19 years [10]. A study in Japan found that a dietary pattern including vegetables, condiments, mushrooms, and red meat was negatively correlated with anemia in elderly individuals aged ≥ 65 years [11]. Although there have been studies investigating the association between dietary patterns and anemia, few articles specifically highlight the characteristics of the dietary patterns of Cantonese cuisine in South China, which is a classic example of Eastern healthy dietary patterns.…”
Section: Introductionmentioning
confidence: 99%